Synthesis, Characterization and Biological Activity of Schiff Base Complexes of Sulfa Drug with Transition Metals - Gomathi, V.; Selvameena, R. (Asian Journal of Chemistry, 2012)
The Schiff base has been prepared by refluxing sulfa pyridine with 2-hydroxynaphthaldehyde in ethanolic media and then complexed with Co(II), Ni(II), Cu(II), Zn(II) and Mn(II) metal ions. The synthesized ligand and complexes were characterized by elemental analysis, molar conductances, magnetic moments, IR, 1H NMR and electronic spectral data. The spectral data of the complexes have revealed bidentate complexing nature of the Schiff base ligand through phenolic oxygen and azomethine nitrogen atoms. The antibacterial and antifungal activity of the Schiff base and its complexes have also been screened. All the metal complexes possess significant to moderate activity and the metal complexes exhibit more activity against various species compared to the Schiff base.